If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5b + 3(3b + 4) = -24 + 2b Reorder the terms: 5b + 3(4 + 3b) = -24 + 2b 5b + (4 * 3 + 3b * 3) = -24 + 2b 5b + (12 + 9b) = -24 + 2b Reorder the terms: 12 + 5b + 9b = -24 + 2b Combine like terms: 5b + 9b = 14b 12 + 14b = -24 + 2b Solving 12 + 14b = -24 + 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. 12 + 14b + -2b = -24 + 2b + -2b Combine like terms: 14b + -2b = 12b 12 + 12b = -24 + 2b + -2b Combine like terms: 2b + -2b = 0 12 + 12b = -24 + 0 12 + 12b = -24 Add '-12' to each side of the equation. 12 + -12 + 12b = -24 + -12 Combine like terms: 12 + -12 = 0 0 + 12b = -24 + -12 12b = -24 + -12 Combine like terms: -24 + -12 = -36 12b = -36 Divide each side by '12'. b = -3 Simplifying b = -3
| x*2-x=20 | | v=(50-2x)(50-2x)(x) | | y=5*cos*2x+11 | | (5z+6)(4-z)=0 | | q-1=5q+3q-8 | | 0.16=-0.4+0.7x | | 8.5+3.4= | | (4z+7)(5+z)=0 | | 1.2=-1.4+20x | | -9x+4y=7 | | 5x-y=14.9 | | 5x+7=-6+2x+19 | | 4x+y-4=0 | | 4x-9=-3x+5 | | 3(4x-2)+5x=30x | | S^2+2s= | | -4x-9=2x+9 | | 2=2.2x-15 | | 5-11p=17 | | 18x-12y+23=0 | | 8.5+3(9-5)= | | -4(7)-2y=-10 | | 3x+(-5x)= | | 55(6x-6)(7x+1)= | | -10x-10(-10)=20 | | y^2+4x+10y+29=0 | | 2e-3=7e-8 | | 6-3(3x-5)=8x-98 | | -0.7(4y-3)+2.3y=-0.3y+2.1 | | 8k-7=11-2k | | 7y-5x=29 | | 2(3x+2)-3=x-39 |